2013
DOI: 10.1097/prs.0b013e3182865977
|View full text |Cite
|
Sign up to set email alerts
|

Breast Reconstruction Modality Outcome Study

Abstract: : Therapeutic, III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
36
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 88 publications
(38 citation statements)
references
References 24 publications
2
36
0
Order By: Relevance
“…Though not reported in this study the number of hours spent performing unilateral and bilateral free flap procedures had decreased by 2–4 hours, 2 years after introducing these procedures. This efficiency is reflected in reports from the practice of an experienced microsurgeon 23 which showed a trend towards lower institutional costs with free flap reconstructions; this study by Fischer et al however did not provide data on professional revenue. One practical solution to the problem of efficient time use for the surgeon who performs free autologous flap procedures is to run multiple rooms.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Though not reported in this study the number of hours spent performing unilateral and bilateral free flap procedures had decreased by 2–4 hours, 2 years after introducing these procedures. This efficiency is reflected in reports from the practice of an experienced microsurgeon 23 which showed a trend towards lower institutional costs with free flap reconstructions; this study by Fischer et al however did not provide data on professional revenue. One practical solution to the problem of efficient time use for the surgeon who performs free autologous flap procedures is to run multiple rooms.…”
Section: Discussionmentioning
confidence: 86%
“…23 However, facility revenue was significantly higher for abdominal free flaps than implant reconstruction ($30,034 vs $14,951, p= 0.0001). In essence free flaps cost more than implant reconstructions but also generated significantly more.…”
Section: Discussionmentioning
confidence: 93%
“…Other studies have also demonstrated lower rates of complications and reconstructive failure with autologous reconstruction . For example, previous research has demonstrated that diabetics have a higher risk of wound healing complications in implant‐based reconstruction, but not autologous based reconstruction .…”
Section: Discussionmentioning
confidence: 99%
“…Complication rates of women undergoing mastectomy have been welldescribed in the literature [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] ; however, with the ever increasing rate of women undergoing mastectomy it is important to ensure that the complication profile is regularly evaluated. We found that increase in mastectomy weight led to a significant increase in overall complications, seroma, surgical site infection, and hospital readmission.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation